Production of staphylococcal enterotoxins C1 and C2 and thermonuclease throughout the growth cycle. - Otero, A (1990)
Synthesis of enterotoxins C1 and C2 and thermonuclease throughout the growth cycle was investigated with Staphylococcus aureus type strains FRI137 and FRI361 and S. aureus isolates M5 (C1) and L2 (C2) of animal origin. Both enterotoxins were produced during the exponential growth phase or at the beginning of the stationary phase. The minimal incubation time (7 to 12 h) and the lowest population (10(7) to 2 x 10(9) CFU/ml) associated with detectable enterotoxin (1 to 6.5 ng/ml) were related to the total amount of toxin produced after 24 h. Thermonuclease was detected in all samples whenever enterotoxins were detected. Furthermore, strain FRI137 produced thermonuclease earlier and at lower cell populations than it did enterotoxin C1. Patterns of enterotoxin and thermonuclease synthesis did not correlate. The concentration of toxins increased throughout the growth cycle, while the concentration of thermonuclease remained constant during the last hours of the growth cycle.